2022-RA-701-ESGO Elucidating mechanisms underlying methotrexate resistance via quantitative proteomics analysis of GTN patient samples and choriocarcinoma cell lines: a crucial role for serine metabolism. (20th October 2022) - Ntavelou, Panagiota; Georgiou, Marina; Maher, Geoffrey; Roy, Rajat; Yu, Sijia; Ajuh, Paul; Kaur, Baljeet; Horowitz, Neil; Berkowitz, Ross S; Elias, Kevin; Seckl, Michael J; Pardo, Olivier E
Abstract : Introduction/Background: Choriocarcinoma is an aggressive type of Gestational Trophoblastic Neoplasia (GTN). Patients with low-risk GTN following a molar pregnancy frequently commence therapy with single-agent methotrexate (MTX). Unfortunately, many develop resistance (MTX-R) and require either another single agent or more toxic combination agent chemotherapy to achieve remission. Understanding the molecular mechanisms of MTX-R may identify interventions to prevent or reverse this. Methodology: We employed proteomics profiling to identify changes that accompany MTX-R in post molar GTN patient samples and in choriocarcinoma cell lines that were either MTX sensitive (MTX-S) or resistant (MTX-R). Results: Quantitative mass spectrometry (MS) analysis revealed that the de novo serine synthesis pathway was one of the most downregulated pathways both in the MTX-R patients and in the resistant choriocarcinoma cell line. Decreased glucose-derived serine synthesis is supported by our findings that choriocarcinoma MTX-R cells have a less active glycolytic pathway. Concomitant de novo serine synthesis inhibition and serine deprivation from the growth medium promoted MTX-R in cell lines. Moreover, examination of the expression levels of 1-Carbon metabolism enzymes suggested a different utilization of serine, the major 1-Carbon donor, between sensitive and resistant cells. In particular, MTX-R cells may be channeling serine into pathways crucial for cell survival, such as the synthesis of glutathione (GSH), as indicated by the increased levels of this metabolite in resistant cells. Conclusion: Upon MTX-R, choriocarcinoma cells favor redirection of serine to GSH production and this may help with combating chemotherapy-induced reactive oxygen species (ROS) accumulation and hence participate in the resistant phenotype. In contrast, MTX-sensitive cells utilize serine for nucleotide synthesis and the maintenance of proliferation. Hence, targeting upstream pathways or molecules that block the synthesis of serine in combination with or without MTX treatment could improve therapeutic response in patients with MTX resistance.